CPC as Indonesia and Malaysia's Response to European Union Protectionism For the 2015 - 2019 Period - Newfreedo Chidlir Erisnesia (Journal of Social Science, 2021)
Crude Palm Oil (CPO) or better known as palm oil is the leading export commodity of Indonesia and Malaysia in improving their country's economy, Indonesia and Malaysia are the largest palm oil producers in the world, production reaches 80% and 20% of them are coconut producing countries. another palm. Palm oil gets quite a lot of importers annually, India and the European Union are the biggest consumers of this palm oil, although the European Union is the largest consumer of palm oil, the European Union has its regulations for palm oil, triggering the RED II Renewable Energy Directive regulation. II which aims to prevent countries in the European Union from using palm oil again in 2020, RED II is considered a form of protectionism. In researching this research, the author uses a qualitative descriptive method, to examine what kind of response was done by Indonesia and Malaysia when they received protectionism policies that had an impact on their export commodities.